Are happy workers more productive? - Eugenio Proto (IZA World of Labor, 2016)
Recently, large companies like Google have made substantial investments in the well-being of their workers. While evidence shows that better performing companies have happier employees, there has been much less research on whether happy employees contribute to better company performance. Finding causal relations between employee well-being and company performance is important for firms to justify spending corporate resources to provide a happier work environment for their employees. While correlational and laboratory studies do find a positive relationship, the evidence remains sparse.
Keywords: J08; D03; C9; 330; productivity; happiness; well-being; experiment